Accountability of School Operational Assistance Program At Senior High School 5 Palopo - Isgunandar, Isgunandar (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
The phenomenon that occurs in the development of the public sector in Indonesia today is the strengthening of accountability demands for public institutions, both at the central and regional levels. This study aims to analyze and describe the accountability of the BOS program at SMA Negeri 5 Palopo and to determine the factors that influence the accountability of the BOS program at SMA Negeri 5 Palopo. The research method used is a qualitative approach with a descriptive research type. Data collection was carried out through observation, in-depth interviews and document reviews. The results of the study indicate that the accountability of the BOS program at SMA Negeri 5 Palopo has been running well, indicated by the publication of the BOS program to parents of students (intentions disclosure), the BOS program at SMA Negeri 5 Palopo is carried out in accordance with the technical instructions of the BOS program (performance based planning), SMA Negeri 5 Palopo provides reports on the use of BOS funds (financial reporting) and there is supervision and evaluation of the BOS program implemented at SMA Negeri 5 Palopo (citizen caution). Furthermore, the factors that influence the accountability of the BOS program at SMA Negeri 5 Palopo are the commitment of the principal of SMA Negeri 5 Palopo and the control of the SMA Negeri 5 Palopo Committee in implementing the BOS program responsibly.